2023
DOI: 10.5435/jaaosglobal-d-23-00005
|View full text |Cite
|
Sign up to set email alerts
|

Injuries Sustained With Falls From Height in Crossing the United States-Mexico Border at a Level I Trauma Center: A Prospective Cohort Study

Abstract: Introduction:The US Department of Homeland Security has reported increases in encounters and apprehensions at the US Southwest border for the past several years. The purposes of this study were to assess the demographics, patterns of injuries, and surgical interventions, associated with falls from height along the US-Mexico border.Methods:A prospective cohort study was conducted at a Level I trauma center from January 2016 through December 2021 of all patients who fell from height crossing the US-Mexico border… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Those who undergo definitive fixation often are either deported or released from U.S. CBP custody after surgery. We have documented a 1-month follow-up rate among these patients of 12.2% 4 . The rest of the patients disperse across the country as local NGOs facilitate their transportation to destinations where they have family.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Those who undergo definitive fixation often are either deported or released from U.S. CBP custody after surgery. We have documented a 1-month follow-up rate among these patients of 12.2% 4 . The rest of the patients disperse across the country as local NGOs facilitate their transportation to destinations where they have family.…”
mentioning
confidence: 80%
“…At our own institution, we have identified an increase in migrant trauma since 2020. Pilon fractures represent the most frequent injury encountered (27.2%) 4 . Compared with the general population, a disproportionate number of young female patients are affected.…”
mentioning
confidence: 99%
“…Polmear and colleagues noted an increase in monthly median border fall admissions from zero in 2016 to 18·5 in 2021 in El Paso, Texas. 14 Patients falling from greater than 18 feet were more likely to have an ISS greater than 15, further highlighting the consequences of raising the border to 30-feet. The Mexican Consulate released a report in January 2023 detailing a similar trend on the other side of the border.…”
Section: Traumatic Injuries At the Us-mexico Bordermentioning
confidence: 97%
“… 1–4 Our institution in El Paso, Texas, is the only Level I trauma center in a 280-mile radius along the U.S.-Mexico border and has observed an increase in patients sustaining falls and injuries traversing the border that require admission and operative management since 2017. 5 The purpose of this study is to report the demographics, incidence, and patterns of spine and concomitant injuries associated with border crossings resulting in fall from height.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has demonstrated that U.S. Border Patrol (USBP) apprehensions correlate with hospital admissions, suggesting that a consistent proportion of migrants sustain injuries in traversing the border. 5 , 10 …”
Section: Introductionmentioning
confidence: 99%